2005
DOI: 10.1111/j.1467-9450.2005.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonally adjusted exposure to cold and darkness on cognitive performance in circumpolar residents

Abstract: The effects of seasonally adjusted 24-h exposure to cold and darkness on cognitive performance in urban circumpolar residents was assessed in 15 male subjects who spent three 24-h periods in a climatic chamber at 65 degrees latitude during the winter (January-March) and/or summer (August-September). Each subject was exposed to three different environmental conditions in random order: (1) 22 degrees C temperature and 500 lx lighting; (2) 10 degrees C temperature and 500 lx lighting; and (3) 10 degrees C tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 42 publications
1
21
0
2
Order By: Relevance
“…On the other hand there is a general agreement on impaired memory retrieval in males, rats (Panakhova et al, 1984; Nuñez et al, 2000) and humans (Coleshaw et al, 1983; O’Brien et al, 2007). Improved (Palinkas et al, 2005; Zheng et al, 2008) or unaffected (Baddeley et al, 1975) performance which was reported after cold exposure causing hypothermia is probably related to the variability in study designs, type (water or air), duration and intensity of cold exposure. Performance in spatial tasks seems to be correlated with the intensity of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand there is a general agreement on impaired memory retrieval in males, rats (Panakhova et al, 1984; Nuñez et al, 2000) and humans (Coleshaw et al, 1983; O’Brien et al, 2007). Improved (Palinkas et al, 2005; Zheng et al, 2008) or unaffected (Baddeley et al, 1975) performance which was reported after cold exposure causing hypothermia is probably related to the variability in study designs, type (water or air), duration and intensity of cold exposure. Performance in spatial tasks seems to be correlated with the intensity of hypothermia.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study ( 9 ), exposure to cold air and dim light was associated with decreased response time on all fi ve cognitive tasks, suggesting that the subjects took less time to complete these tasks as environmental conditions became progressively more severe. However, accuracy on complex cognitive tasks improved, whereas accuracy on simple tasks declined.…”
Section: Discussionmentioning
confidence: 97%
“…These tasks included: matching-to-sample, simple reaction time, serial addition/ subtraction, grammatical reasoning, and repeated acquisition of response sequences. The tasks have been described in more detail in our previous study ( 9 ). The tasks were completed in the same order as presented above at each administration; however, the sequence of trials for each task was randomly ordered, so that no subject was administered a particular sequence of trials more than once for any task.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Muscle co-ordination and manual dexterity are impaired, physical load is increased, strength and velocity are decreased and postural sway is increased by cold exposure [3,4,5]. Mental performance is also affected, especially performance in complex tasks [6,7,8]. Wind, wetness and cold materials increase the cooling rate of skin and tissues, and thus increase the adverse effects of cold [9].…”
Section: Cold Workmentioning
confidence: 99%